Best practice guide on the control of lead in drinking water - Hayes, Colin (IWA Publishing, 2010)
The Best Practice Guide on the Control of Lead in Drinking Water brings together, for the first time, all of the regulatory, health, monitoring, risk assessment, operational and technological issues relevant to the control of lead in drinking water. The Best Practice Guide on the Control of Lead in Drinking Water brings together, for the first time, all of the regulatory, health, monitoring, risk assessment, operational and technological issues relevant to the control of lead in drinking water.
Keywords: Water -- Purification -- Lead removal.; Drinking water -- Lead content.; Water-supply -- Environmental aspects.; Water resources development -- Environmental aspects.; Water utilities -- Management.; elektronické knihy; electronic books